Coercive Contract Enforcement: Law and the Labor Market in Nineteenth Century Industrial Britain - Naidu, Suresh; Yuchtman, Noam (American Economic Review, 2013)
British Master and Servant law made employee contract breach a criminal offense until 1875. We develop a contracting model generating equilibrium contract breach and prosecutions, then exploit exogenous changes in output prices to examine the effects of labor demand shocks on prosecutions. Positive shocks in the textile, iron, and coal industries increased prosecutions. Following the abolition of criminal sanctions, wages differentially rose in counties that had experienced more prosecutions, and wages responded more to labor demand shocks. Coercive contract enforcement was applied in industrial Britain; restricted mobility allowed workers to commit to risk-sharing contracts with lower, but less volatile, wages. (JEL J31, J41, K12, K31, N33, N43)